2021
DOI: 10.1186/s12870-021-03291-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptomic and metabolomic analysis of D-leaf of seven pineapple varieties differing in N-P-K% contents

Abstract: Background Pineapple (Ananas comosus L. Merr.) is the third most important tropical fruit in China. In other crops, farmers can easily judge the nutritional requirements from leaf color. However, concerning pineapple, it is difficult due to the variation in leaf color of the cultivated pineapple varieties. A detailed understanding of the mechanisms of nutrient transport, accumulation, and assimilation was targeted in this study. We explored the D-leaf nitrogen (N), phosphorus (P), and potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…However, the tested pineapple species did not significantly differ in N, K, or Na content. This result also coincides with the finding of Chen, Zeng, and Zhang [ 3 ]. Shu et al [ 17 ] observed both translucent and non-translucent pineapple pulp have similar total sugar content, but the translucent pulp has higher apoplastic sugar content.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the tested pineapple species did not significantly differ in N, K, or Na content. This result also coincides with the finding of Chen, Zeng, and Zhang [ 3 ]. Shu et al [ 17 ] observed both translucent and non-translucent pineapple pulp have similar total sugar content, but the translucent pulp has higher apoplastic sugar content.…”
Section: Discussionsupporting
confidence: 93%
“…The HPLC had an analysis column (Fast Carbo-hydrate, 100 × 7.8 mm, Bio-Rad Laboratories, Hercules, Calif). N, P, and K contents were measured using the method described by Chen, Zeng, and Zhang [ 3 ] and were expressed as percent content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, high acidity and toxicity inhibited plant growth changed the structure and diversity of microorganism [2,[10][11][12][13][14]. P plays a vital role in pineapple growth; this means that P is defcient, and plant growth and quality are afected adversely [15]. However, the isolated and selected bacteria strains should possess properties as biofertilizers and bioremediators.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between pineapple yield and soil properties: As claimed by Cunha et al [ 29 ] and Chen et al [ 49 ], concentrations of N, P, K, Ca, and Mg nutrients are undeniably crucial for plants to grow and develop. Fig.…”
Section: Discussionmentioning
confidence: 99%